Routing Hole Mitigation by Edge based Multi-Hop Cluster-based Routing Protocol in Wireless Sensor Network - Sama, Najm Us; Kartinah, Binti Zen; Atiq, Ur Rahman; Baseerat, Bibi (International Journal of Computer Science and Information Security, 2019)
In Wireless sensor network (WSNs) due to the harsh environments the degradation of energy is major issue. For addressing this issue, clustering techniques equalize energy utilization by distributing the workload among different clusters but energy-unaware path selection in multi-hop clustering technique leads to routing hole problem. To reduce the routing hole problem in WSNs, an energy-efficient least-edge computation (ELEC) cluster-based algorithm is proposed, which consider the value of edge count, link cost and energy level in selecting the next hope neighbor in data transmission. Results of our simulation reveal that ELEC achieves nearly double network lifetime by equal energy consumption in various parts of the network in addition just 5% energy left unused, as compared to existing routing strategies such as LEACH, GRACE, and AODV-EHA. Furthermore the percentage of node failure is half of the other existing routing strategies and 60% of packet drop noticeable decrease is noticed in ELEC as compared to GRACE, LEACH, and AODV-EHA.